HAKIKAT ILMU DALAM PEMIKIRAN ISLAM - Kuswanjono, Arqom (Jurnal Filsafat "WISDOM", 2016)
This research, entitled Essence of Religion in Islam. Many people often connote science with Western. However, if tracked historically, Islam have enormous contribution in developing of science. Therefore, this study aimed to compare the scientific character of the West and Islam, analyzing the development of science in Islamic and discover the nature of science in Islam. This is a library research using hermeneutic method with method elements are description, verstehen and interpretation. The material object is Islamic thought while the formal object is the philosophy of science. The results of this research indicate that there is a distinctive characteristic between Western science and Islam from the aspect of ontology, epistemology, and axiology. The most striking difference is the recognition of the existence of God. In its development, Islamic science actually stems from the Prophet Muhammad's own then forwarded the new companions subsequent Islamic thinkers. The nature of science in Islam includes facility, processes and objectives. Epistemologically, it means that Islam accepts ratio and sense as well as revelation and intuition, while the purpose of science is to reveal the truth in pursuit of Ultimate Truth.